2020
DOI: 10.1177/0265407520944243
|View full text |Cite
|
Sign up to set email alerts
|

The dyadic influences of mindfulness on relationship functioning

Abstract: Using family stress and coping theory, the current study assessed dyadic influences of specific facets of mindfulness ( nonreactivity, acting with awareness, and nonjudgment), accounting for stress levels, on relationship quality and sexual satisfaction in an ethnically and economically diverse sample of 847 married and unmarried heterosexual couples. Results from actor–partner interdependence models indicated a positive association between one’s own report and partners’ report of nonreactivity and one’s own r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Research on the role of mindfulness and couple relationships has demonstrated that mindfulness is associated with more pro-relationship behaviors, relationship satisfaction, and relationship quality. Indeed, our findings are consistent with prior findings noting the role of mindfulness in promoting couple dynamics and increased relationship quality (Adair et al, 2018; Erkan et al, 2021; Karremans et al, 2017; McGill & Adler-Baeder, 2020; McGill et al, 2016, 2020; Pepping & Halford, 2016). Yet, this body of research has scarcely incorporated strongly relational theories to outline the importance of mindfulness for couple relationships, has mostly been conducted at the individual level, and has often used narrow conceptualizations of relationship quality (Harvey et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Research on the role of mindfulness and couple relationships has demonstrated that mindfulness is associated with more pro-relationship behaviors, relationship satisfaction, and relationship quality. Indeed, our findings are consistent with prior findings noting the role of mindfulness in promoting couple dynamics and increased relationship quality (Adair et al, 2018; Erkan et al, 2021; Karremans et al, 2017; McGill & Adler-Baeder, 2020; McGill et al, 2016, 2020; Pepping & Halford, 2016). Yet, this body of research has scarcely incorporated strongly relational theories to outline the importance of mindfulness for couple relationships, has mostly been conducted at the individual level, and has often used narrow conceptualizations of relationship quality (Harvey et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Mindfulness meditation is becoming increasingly popular because of its promise to influence several integrated metrics of overall health—attentional control [ 33 ], emotion dysregulation [ 93 , 94 ], perceived and objective markers of stress [ 95 , 96 ], loneliness [ 97 , 98 ], systemic markers of peripheral inflammation [ 82 ], and relationship quality [ 99 ]. The adaptation of mindfulness programs to a variety of settings was also catapulted by the increasing rise of stress and mental health problems during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Norton's Quality of Marriage Index was used to assess relationship satisfaction among participants (Norton, 1983). Although this is nominally focused on measuring marriage quality, this measure has been used to assess relationship quality in nonmarital romantic relationships (McDaniel & Coyne, 2016;McGill et al, 2020). In the current study, the authors replaced the term "spouse" for "partner" and "marriage" for "relationship."…”
Section: Relationship Satisfactionmentioning
confidence: 99%